THE INFLUENCE OF 10% TRICHLOROACETIC ACID ON COVERING OF TYMPANIC MEMBRANE PERFORATION WITHOUT BRIDGE - Wahju Budi Martono; Jogjahartono -; Noor Pramono (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2008)
Background: Up to now, the covering of tympanic membrane perforation on human either or without operation has always been using the bridge. The covering of tympanic membrane perforation without operation by attempting epithelization of perforation edge which initially perform by injuring the perforation edge. The material that can be used to make the injuring is 10% trichloroacetic acid (TCA). The covering of perforation without bridge was conductive on guinea pig and proven that spontaneous covering take place. And there for the covering of tympanic membrane perforation without bridge can also happened on human being, by making the injuring on the perforation edge using 10% TCA.Objective: The objective of the research to prove that application of 10% TCA on the edge of tympanic membrane perforation can cause the perforation covering although without using the bridge.Method: This is the experimental research using pre and post test design. The chronic tympanic membrane perforation patiens without infection with normal Eustachii tube function, the size of tympanic membrane perforation 25% were treated with 10% TCA application on their perforation edge every 2 weeks until the covering take place or maximal 5 times application if no covering take place. Measurement of perforation size was conducted prior to first application and after the treatment.Result: From 36 ears suffering chronic tympanic membrane perforation with normal Eustachii tube function and without infection with the size of perforation 25% were selected to the sample of the research. The perforation that can be covered after the treatment of 10% TCA application were higher in number than those were not covered (63,9%:39,1%).Conclusion: The application of 10% TCA on the edge of tympanic membrane perforation can cause perforation covering although without the use of bridge.Keywords: Tympanic membrane perforation, Trichloroacetic acid